Mission Statements, Values, and Practice: The Case of Love of Learning - Herman, Jamie (Philosophical Inquiry in Education, 2025)
‘Love of learning’ is a phrase that appears frequently in school mission statements, among others with similar connotations. Using ‘Love of learning’ as a case, I employ comparative conceptual analysis to characterize the value underlying the phrase before reviewing the implications this holds for practice in schools that use the phrase in their mission statements. I argue ‘Love of learning’ refers to a distinct, intrinsically valuable phenomenon that implies a particular type of learning experience. A commitment to fostering ‘love of learning’ at school would require developing environments conducive to each student having this particular learning experience. This carries implications for practice, particularly in schools that include fostering ‘love of learning’ in their mission statements. As a case, the conceptual analysis of ‘love of learning’ presented here demonstrates the need to review mission statements to assess whether values conveyed therein align with institutional practices.